2000
DOI: 10.1002/(sici)1521-3749(200005)626:5<1112::aid-zaac1112>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Structure Structure D 2000Ternary Aluminides with the Ideal Composition A 2 Pt 6 Al 15 (A: Y, Gd-Tm, Zr).-The title compounds are prepared by arc melting of the elements followed by annealing in a high-frequency furnace. The structures of the compounds are determined by powder XRD. Single crystal data are reported for Y1.357Pt4Al9.99 and Zr1.00Pt4Al10.22 (hexagonal, space group P63/mmc, Z = 1). -(NIERMANN,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 0 publications
6
20
0
2
Order By: Relevance
“…The fcc-box has the lattice constant of 15Å. The cohesive energy Ec of CoxPy can be expressed as follows [29][30][31]: [33] Hexagonal hP9 9 P-62m CoP [34] Orthorhombic oP12 8 Pnma CoP2 [35] Monoclinic mP12 12 P121/c1 CoP3 [36] Cubic cI32 16 Im-3 [32] b = 3.507 c = 6.607 [32] c = 6.587…”
Section: Methodssupporting
confidence: 70%
“…The fcc-box has the lattice constant of 15Å. The cohesive energy Ec of CoxPy can be expressed as follows [29][30][31]: [33] Hexagonal hP9 9 P-62m CoP [34] Orthorhombic oP12 8 Pnma CoP2 [35] Monoclinic mP12 12 P121/c1 CoP3 [36] Cubic cI32 16 Im-3 [32] b = 3.507 c = 6.607 [32] c = 6.587…”
Section: Methodssupporting
confidence: 70%
“…Their crystal structure was determined for LaFe 4 P 12 . Some twenty phosphides are known to crystallize with this structure type, where iron may be substituted by its homologues ruthenium and osmium 71. 76 They were originally prepared from the elemental components in a tin flux with the atomic ratio RE : T :P:Sn=1:4:20:50 in sealed silica tubes by slowly heating (to avoid violent reactions!)…”
Section: The Tin Fluxmentioning
confidence: 99%
“…39 The experimental values of this study show good agreement with those reported earlier. [40][41][42] Samples for transmission electron microscopy ͑TEM͒ and electron energy loss spectroscopy ͑EELS͒ were prepared by grinding in ethanol in an agate mortar and deposited on a carbon film suspended on a copper mesh. The composition of the samples was then checked using energy dispersive x-ray analysis ͑EDS͒ in a JEOL 2000FX TEM operated at 200 kV fitted with a Tracor Northern EDS detector and a Noran System Six analysis system.…”
Section: A Synthesis and Sample Preparationmentioning
confidence: 99%